2020
DOI: 10.1002/ijfe.2209
|View full text |Cite
|
Sign up to set email alerts
|

Innovation—Unemployment Nexus: The case of EU countries

Abstract: In order to achieve a sustainable growth and development process in a globalised competitive environment, the effect of monitoring the technological developments of the national economies is a necessity. Innovation, shown as a cause of technological developments, contributes to the transformation of technology into social and economic benefits. Innovation changes the structure of employment. However, there is no consensus in the literature about how innovation affects employment. Some suggest that technologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Morrison and Siegel (2001) and Kim and Kim (2020) observed a positive relationship between R&D expenditures and employment of high-skill labor. Fagerberg et al (1997), Van Roy et al (2018), andYildirim et al (2020) all documented a positive relationship between R&D and labor, whereas Van Roy et al (2018) found that this only holds in high-but not in low-tech industries. Vainiomaki and Laaksonen (1999) found that high-technology sectors, measured by R&D intensity, have the highest job creation rates.…”
Section: Studies Supporting the Reinstatement Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Morrison and Siegel (2001) and Kim and Kim (2020) observed a positive relationship between R&D expenditures and employment of high-skill labor. Fagerberg et al (1997), Van Roy et al (2018), andYildirim et al (2020) all documented a positive relationship between R&D and labor, whereas Van Roy et al (2018) found that this only holds in high-but not in low-tech industries. Vainiomaki and Laaksonen (1999) found that high-technology sectors, measured by R&D intensity, have the highest job creation rates.…”
Section: Studies Supporting the Reinstatement Effectmentioning
confidence: 99%
“…Twenty studies fall into the residual category other/indirect. Among these, Fagerberg et al (1997), Feldmann (2013, Kim and Kim (2020), Morrison and Siegel (2001), Vainiomaki and Laaksonen (1999), Van Roy et al (2018), andYildirim et al (2020) used R&D expenditures or patents as a measure of technological change. Morrison and Siegel (2001) and Kim and Kim (2020) observed a positive relationship between R&D expenditures and employment of high-skill labor.…”
Section: Studies Supporting the Reinstatement Effectmentioning
confidence: 99%
“…Using World Bank data for the years 1998-2015, Yildirim et al (2022 clustered 12 European countries into two groups according to their innovation levels. By adopting panel threshold regressions, they find that innovation (measured by patent applications) increases unemployment across both groups of countries, although the negative impact is more pronounced in countries with low-innovation regimes.…”
Section: Previous Literaturementioning
confidence: 99%
“…The panel threshold model of Yildirim et al (2020) shows that technological development increases the unemployment rate for the period of 1998-2015 in EU countries. Bordot (2022) found that a 10% increase in the stock of industrial robots is associated with a 0.42-point increase in the unemployment rate in OECD countries between the years 2005 and 2017.…”
Section: Previous Empirical Studiesmentioning
confidence: 99%
“…Although there is a wide range of empirical literature, there is no consensus on the relationship between technology and unemployment (Yildirim, Yildirim, Erdogan & Kantarci, 2020). To grasp this, it is vital to determine the two competing effects technology exercises on employment.…”
Section: Introductionmentioning
confidence: 99%